Tectonic evolution of the Gabal Loman area, North Eastern Desert, Egypt: implications from low-temperature multithermochronometry on the Arabian-Nubian shield - Mansour, Sherif; Gharib, Mohamed A.; Hasebe, Noriko; Abdelrahman, Kamal; Fnais, Mohammed S.; Tamura, Akihiro (Frontiers in Earth Science, 2023)
The Neoproterozoic Arabian-Nubian Shield (ANS) in the Egyptian Eastern Desert envelops the regional tectonic history since its formation till the Red Sea/Gulf of Suez development in Oligocene-Miocene times. Application of multithermochronometry techniques has proven to be a successful approach to revealing the influence and extent of each regional tectonic event and reconstruct the thermo-tectonic history of the studied region. Therefore, representative samples from the ANS basement rocks of Gabal Loman area at the western flank of the northern Red Sea were collected. Zircon fission-track data reveals Carboniferous cooling ages. While, apatite fission-track data represents three cooling age spans of Cretaceous and Eocene-Oligocene. Integration of these data with time-temperature history modelling reveals three different cooling events developed in response to regional tectonic events; (1) the Devonian-Carboniferous Hercynian tectonic event which affected the region with rocks exhumation of ca. 4.2 ± 1.4 km, (2) the Gondwana breakup initiation which affected the region with localized uplifts, and (3) the Oligocene-Miocene northern Red Sea rift initiation which caused flanks uplift in the studied region of ca. 1.2 ± 0.4 km. This modest rift flank uplift suggests a passive rift with a dominant mechanical component for the northern Red Sea rifting in the region of study.